2021
DOI: 10.1044/2021_ajslp-19-00215
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Comparison of In-Person and Telepractice Evaluations of Stuttering

Abstract: Purpose The purpose of this study was to compare in-person and telepractice evaluations of stuttering with adult participants. The research questions were as follows: Is an evaluation for stuttering via telepractice equivalent to an in-person evaluation in terms of (a) duration of individual evaluation tasks and overall length of the evaluation, (b) clinical outcomes across evaluating clinicians, and (c) participant experience? Method Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Unfortunately, although assessment is the first step before management, to date not a single study can be found in which the viability of TP stuttering assessments of children is evaluated (Lowe et al., 2013; McGill et al., 2019). One study on adults could be traced, which compared in‐person and TP evaluations of stuttering with 14 adult participants (McGill et al., 2021). The results of this study suggested that TP evaluations of stuttering were comparable with in‐person evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, although assessment is the first step before management, to date not a single study can be found in which the viability of TP stuttering assessments of children is evaluated (Lowe et al., 2013; McGill et al., 2019). One study on adults could be traced, which compared in‐person and TP evaluations of stuttering with 14 adult participants (McGill et al., 2021). The results of this study suggested that TP evaluations of stuttering were comparable with in‐person evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Choi와 Sung (2014) 2003;Jonkers & Bastiaanse, 1996;Kemmerer & Tranel, 2000;Kim & Thompson, 2000;Luzzatti et al, 2002;Thompson, Lange, Schneider, & Shapiro, 1997). 국내에서도 실어증 환자와 정상 성인 을 대상으로 논항 구조에 따른 동사 이름대기 수행 능력을 살펴보 았는데 (Yoon & Sung, 2020) (Thompson, 2003), 이러한 복잡성에 따라 정상 노년층 및 신경언어장애 집단의 동사 산출 수행력이 달라질 수 있다 (Kim & Thompson, 2000;Sung & Kwak, 2012) (Crutchley & Campbell, 2010;Dekhtyar, Braun, Billot, Foo, & Kiran, 2020;McGill, Siegel, & Noureal, 2021) (Choi et al, 2021;Dekhtyar et al, 2020;Theodoros et al, 2008) Kemmerer & Tranel, 2000;Kim & Thompson, 2000;Luzzatti et al, 2002;Thompson et al, 1997) (Barresi et al, 1999;Mortensen et al, 2006;Ramsay et al, 1999;Sung & Kim, 2011)…”
unclassified